The Effect of Adding Vitamin C to drinking Water In Some Biochemical Parameters Broiler Chickens by Heat stress (Journal of Hama University, 2019)
This study was carried out on ninety (90) one-day old unsexedone of the commercial crossed of broiler chicken were used in this experiment which lasted for 45 days. This study which aimed to study the effect of adding different levels of Vitamin C in drinking water in some Biochemical Parameters Broiler Chickens by Heat stress.The chicks were randomly  distributed into three groups each contained( 30) chicks. three groups were used as follows :G1 Control No vitamin c added , G2 Adding 150mg vitamin c\Liter water , G3Adding 200mg vitamin c\Liter water , feed and water were Ad Libitum .The results showed the significant increase (P